An ex-post evaluation of agricultural extension programs for reducing fertilizer input in Shaanxi, China - Hua, Chunlin; Woodward, Richard T.; You, Liangzhi (MDPI, 2017)
It is difficult to control agricultural Non-point Source (NPS) pollution, caused by overusing of chemical fertilizer, through laws alone. An agricultural extension program is an alternative way to reduce fertilizer input. This paper estimates the average change in fertilizer use of farmers, which is attributable to their participation in the agricultural extension program. The Inverse-Probability Weighted matching method is used to evaluate the average treatment effect for the farmers who engaged in the program and, to a limited extent, evaluate the impact of individual elements of the program. Surprisingly, we find that farmer-to-farmer training may have had a counterproductive effect while the posters may be the most effective program element in reducing fertilizer use in the context.